Headache in transient ischemic attacks - Elena R. Lebedeva (The Journal of Headache and Pain, 2018)
Abstract Background Headache is a common feature in acute cerebrovascular disease but no studies have evaluated the prevalence of specific headache types in patients with transient ischemic attacks (TIA). The purpose of the present study was to analyze all headaches within the last year and the last week before TIA and at the time of TIA. Methods Eligible patients with TIA (n = 120, mean age 56.1, females 55%) had focal brain or retinal ischemia with resolution of symptoms within 24 h without presence of new infarction on MRI with DWI (n = 112) or CT (n = 8). All patients were evaluated within one day of admission by a single neurologist. As a control group we used patients (n = 192, mean age 58.7, females 64%) admitted with diagnoses “lumbago”, “lumbar spine osteochondrosis” or “gastrointestinal ulcer”. Results One-year prevalence of migraine without aura was significantly higher in TIA patients than in controls: 20.8% and 7.8% respectively (p = 0.002, OR 3.1, 95% CI 1.6–6.2). 22 patients (18.3%) had sentinel or warning headache within the last week before TIA. At the time of TIA a new type of headache was observed in 16 patients (13.3%). No controls had a new type of headache. 12 of these 16 patients had migraine-like headache, 8 patients had tension-type-like headache and one patient thunderclap headache. Posterior circulation TIA was associated with headaches within last week before TIA and at the time of TIA much more frequently than anterior circulation TIA. Conclusions The one year prevalence of migraine was significantly higher in TIA patients than in controls and so was the prevalence of headache within the last week before TIA and at the time of TIA. A previous headache that worsens and a new type of headache can be a warning of impending TIA.